A Rapid Prototyping for Wireless Virtual Network Embedding using MARVELO - Afifi, Haitham; Karl, Holger; Eikenberg, Sebastian; Mueller, Arnold; Gansel, Lars; Makejkin, Alexander; Hannemann, Kai; Schellenberg, Rafael (2019 IEEE Wireless Communications and Networking Conference (WCNC) (IEEE WCNC 2019) (Demo))
One of the major challenges in implementing wireless virtualization is the resource discovery. This is particularly important for the embedding-algorithms that are used to distribute the tasks to nodes. MARVELO is a prototype framework for executing different distributed algorithms on the top of a wireless (802.11) ad-hoc network. The aim of MARVELO is to select the nodes for running the algorithms and to define the routing between the nodes. Hence, it also supports monitoring functionalities to collect information about the available resources and to assist in profiling the algorithms. The objective of this demo is to show how MAVRLEO distributes tasks in an ad-hoc network, based on a feedback from our monitoring tool. Additionally, we explain the work-flow, composition and execution of the framework.
Keywords: WSN; virtualization; VNE